Mapping research on second language writing teachers: A review on teacher cognition, practices, and expertise. (October 2022) - Zheng, Yao; Yu, Shulin; Liu, Chunhong; Jiang, Lianjiang
Abstract: The increasing scholarly attention on L2 writing teachers necessitates a review of the studies targeting L2 writing teachers to provide a comprehensive mapping of the field. This paper thus reviews empirical research on L2 writing teachers (1980–2020), following a thematic and content analytic approach. Sixty-seven empirical studies were examined and the results identified three major lines of inquiry: teacher cognition, teaching practice, and teacher expertise. The first line involves research on L2 writing teacher cognition, which includes but is not limited to teacher beliefs, attitudes, awareness, identity, and preferences. The second line embraces studies on L2 writing teacher practices reporting a range of instructional practices, feedback, and assessment practices across contexts. The third aspect focuses on L2 writing teacher expertise, which is mainly exhibited in L2 writing teachers' employment of pedagogic strategies, implementation of innovations, and engagement with professional development. Based on the systemic review, the paper proposes a coherent theoretical framework to conceptualize L2 writing teacher cognition, practice, and expertise for further research on L2 writing teachers. Implications are also discussed on how L2 writing teachers can be better prepared through purposeful professional development initiatives.